Assessment of energy demand in Laser sailing: influences of exercise duration and performance level - Castagna, O.; Brisswalter, J. (European Journal of Applied Physiology, 2007)
In this study we analyzed the influence of both exercise duration and skill level on energy demand in Laser sailing. Twenty-three subjects volunteered for this study. The population is divided into two groups according to their skill level: 13 high (HS) and 10 low (LS). Every subject performed a 30 min upwind sailing test, with a tacking every 2 min. Heart rate (HR), gas exchange and respiratory parameters were analyzed throughout the trial, and measured blood lactate concentration ([Labl] at rest and immediately after the exercise completion. Three, 4 min intervals were selected for analysis: 6-10 min (T10), 16-20 min (T20) and 26-30 min (T30). In contrast to previous studies, we found significantly progressive aerobic energy metabolism with sailing duration in the HS group (T10 = 45%; T20 = 61%; T30 = 68% P < 0.05), whereas this demand remained stable, and significantly lower in LS group (T10 = 45%; T20 = 52%; T30 = 51% P < 0.05). This study shows that aerobic demand is significantly more important in LS than in HS subjects after 30 min regatta, and could be an important factor in Laser regatta performance. We need further studies to confirm and explain this difference.